Propagandni fond za Koroško - Hönig, Nataša (Prispevki za novejšo zgodovino, 2024)
The establishment of the Kingdom of Serbs, Croats and Slovenes in 1918 opened up opportunities for a new economic policy characterised by the “nationalization” or “slovenization” of economic entities under “foreign” administration or owned by “foreigners”. The National Committee for Carinthia confiscated or "sequestered" a large amount of lead in Mežica and channelled the money from the sale to the Propaganda Fund for Carinthia. In 1922, representatives of the liberal Yugoslav Democratic Party were misusing money from the lead business, which triggered the affair. The article focuses on the intertwining of economy and politics by creating the northern border and the complex and long-term consequences of the “lead manipulation”.
Keywords: Gregor Žerjal; Jadran bank; Jadranska banka; Jugoslovanska demokratska stranka; Kingdom SCS; Kraljevina SHS; Mežica lead mine; mežiški rudnik svinca; propagandni fond za Koroško; the Propaganda Fund for Carinthia; Yugoslav Democratic Party